Business Development Strategy of Putri Mas Awal in Tegal Sari Mandala III Medan Denai District - Shintia Putri Aisyah; Annaisaburi Annaisaburi (UNIVERSITAS PAKUAN, 2023)
Putri Mas business is a restaurant named